Desarrollo e implementación de una aplicación móvil en sistemas android para la geolocalización de tricimotos en tiempo real para la compañía 19 de mayo del cantón La Maná. - Díaz Díaz, Elías David (2021)
This project will develop a mobile application that allows requesting a transport unit known as Tricimotos, from an end user and that allows a driver to reserve a transport request, Android Studio, Java language and Firebase will be used as the database in time real. We will use Geopositioning technology to determine the position of where the order is made, this will allow us to monitor orders or requests from clients to the company in question to make the corresponding trips from both the client's application and that of the driver once it exists the route acceptance process. Which the project will be based on the implementation of a mobile application, the users in which they will be able to reserve a unit of the Company and the driver will be able to see the requests of the users that they request for their transfer. Android Studio will be used as the development environment, as the Java programming language and Google's Firebase product, which will integrate several highly important modules into the Google Platform cloud services.